Penerapan Keadilan Restoratif Terhadap Anak Yang Berkonflik Dengan Hukum: (Studi Putusan No. 38/Pid.Sus-Anak/2022/PN Bekasi) - Novitria Haryani; Trias Saputra (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
In the juvenile criminal justice process, protection of children must be prioritized. As in the provisions of UU No. 11 of 2012 concerning the Juvenile Criminal Justice System, which is a new chapter for the juvenile criminal justice system, which initially prioritized punitive retaliation in order to provide a deterrent effect, to prioritizing a restorative justice approach. However, currently there are still many court decisions against children in conflict with the law in the form of imprisonment, even though imprisonment is a form of deprivation of liberty and is the last option among other sanctions. This shows that even though there is a Juvenile Justice System Law, it does not mean that law enforcement is complete and perfect, there is still a need for the role of other factors, namely the family, community and law enforcement officials in implementing juvenile justice which prioritizes restorative justice. For example, in Decision No. 38/Pid.Sus Anak/2022/PN Bekasi, the child was sentenced to 4 months in prison because he was found to have a sharp weapon. In fact, restorative justice efforts should be implemented before continuing the case to the judicial process, so that children can be given the opportunity to be responsible for what they have done and do not need to experience psychological trauma due to the judicial process or imprisonment.